2021
DOI: 10.1108/pm-05-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Model for promoting green certification of buildings in developing nations: a case study of Nigeria

Abstract: PurposeSeveral studies have shown that climate change is a threat to sustainable human living and high consumption of energy by buildings is a contributory factor. However, green practices in buildings have been proved as one of the successful technologies to mitigate global warming. Previous studies have shown lax green practices in developing countries’ buildings, but how far concerning green certification of buildings in Nigeria is yet to be explored. Therefore, this paper investigated the barriers to green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Harmonizing green building standards and certifications globally is essential for ensuring consistency and promoting the adoption of sustainable building practices , Ebekozien, et. al., 2022.…”
Section: International Cooperation and Collaborationmentioning
confidence: 99%
“…Harmonizing green building standards and certifications globally is essential for ensuring consistency and promoting the adoption of sustainable building practices , Ebekozien, et. al., 2022.…”
Section: International Cooperation and Collaborationmentioning
confidence: 99%
“…Dadzoe et al [20] and Anzagira et al [18] identified a lack of awareness as one of the limiting factors hindering the uptake of GB in Sub-Saharan Africa. Other impediments include but are not limited to inadequate training and education, existing policy/regulation, implementation capability, higher initial costs of green construction practices and materials [16,18,[21][22][23][24], lack of integration of local culture, traditional construction methods [18,19,25], and challenges related to design and construction implementation of green building processes [19,22,24]. Inferring from the cited literature, low GBP uptake seems to be a crosscutting feature prevailing in most African countries.…”
Section: Barriers and Drivers Of Green Building Uptake In Africamentioning
confidence: 99%
“…In Nigeria, Opoko et al [67] advocates for an intensive campaign to raise awareness of the tremendous benefits of green practices. According to Ebekozien et al [23] and Komolafe and Oyewole [68], awareness and sensitization regarding green building certification is a crucial driver promoting GB practices. While stakeholders consider increased awareness among stakeholders (DG08) to be the most important perceived driver, there is still limited uptake of GBP due to a lack of knowledge and awareness on the advantages of GBRS.…”
Section: Perceived Drivers Of Green Building Practices In Tanzaniamentioning
confidence: 99%